Design and Implementation of a 1.5Gsps Digital Channelized Receiver - Xu, Shichao; Liu, Guoman; Gao, Meiguo; Qin, Guo Jie (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Based on the derivation of the efficient implementation structure of the frequency domain polyphase filter digital channelized receiver, a digital channelized receiver was achieved on the hardware platform with I/Q sampling, 1500Msps, 64channels. In order to ensure good performance of the system, optimization of the processor speed and processor resources was fully considered during the design process of the whole system. The actual ultra-wideband signal test results show that the digital channelized receiver is in good performance.